Systematic Literatur Review: Software Tuxmath Sebagai Media Belajar untuk Mengetahui Kemampuan Komputasi Peserta Didik - Nurhalimah Nurhalimah; Yahfizham Yahfizham (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Computational ability is one of the basic skills that is very important for students in learning mathematics. However, many students face difficulties in understanding mathematical concepts due to the lack of interactive and fun exercises. To overcome this, TuxMath is present as an educational game-based software specifically designed to improve students' arithmetic skills through challenging and interesting games. This study aims to evaluate the effectiveness of TuxMath in improving students' computational abilities, through literature reviews and empirical analysis of previous studies. The method applied is the Systematic Literature Review (SLR), by investigating various journals, articles, and studies published between 2020 and 2024. The results of the study show that the use of TuxMath can increase the speed and accuracy of students' arithmetic calculations, increase learning motivation, and help them understand mathematical concepts in a more enjoyable way.